High-Resolution Magic-Angle Spinning NMR Spectroscopy for Evaluation of Cell Shielding by Virucidal Composites Based on Biogenic Silver Nanoparticles, Flexible Cellulose Nanofibers and Graphene Oxide - Stanisic, Danijela; Cruz, Guilherme C. F.; Elias, Leonardo Abdala; Tsukamoto, Junko; Arns, Clarice W.; Soares da Silva, Douglas; Mochkalev, Stanislav; Savu, Raluca; Tasic, Ljubica (Frontiers in Bioengineering and Biotechnology, 2022)
Antiviral and non-toxic effects of silver nanoparticles onto in vitro cells infected with coronavirus were evaluated in this study using High-Resolution Magic-Angle Spinning Nuclear Magnetic Resonance (HR-MAS NMR) spectroscopy. Silver nanoparticles were designed and synthesized using an orange flavonoid - hesperetin (HST) - for reduction of silver(I) and stabilization of obtained nanoparticles. The bio-inspired process is a simple, clean, and sustainable way to synthesize biogenic silver nanoparticles (AgNP@HST) with diameters of ~20 nm and low zeta potential (-40 mV), with great colloidal stability monitored for two years. The nanoparticles were used for the fabrication of two types of antiviral materials: colloids (AgNP@HST spray) and 3D flexible nanostructured composites. The composites, decorated with AgNP@HST (0.05 mmol L-1), were made using cellulose nanofibers (CNF) obtained from orange peel and graphene oxide (GO), being denominated CNF@GO@AgNP@HST. Both materials showed high virucidal activity against coronaviruses in cell infection in vitro models and successfully inhibited the viral activity in cells. HR-MAS 1H-NMR technique was used for determining nanomaterials' effects on living cells and their influences on metabolic pathways, as well as to study viral effects on cells. It was proven that none of the manufactured materials showed toxicity towards the intact cells used. Furthermore, viral infection was reverted when cells, infected with the coronavirus, were treated using the as-fabricated nanomaterials. These significant results open possibilities for antiviral application of 3D flexible nanostructured composite such as packaging papers and filters for facial masks, while the colloidal AgNP@HST spray can be used for disinfecting surfaces, as well as a nasal, mouth, and eye spray.